Important documents on security and diplomacy - Gupta, Arvind, 1953-; Chaturvedi, Mukul; Joshi, Akshay; India. National Security Council Secretariat (New Delhi : Manas Publications published in collaboration with National Security Council Secretariat, 2005)
Sources on foreign relations, national security, and diplomacy.
Inlcudes index.
Keywords: National security -- India -- Sources; India -- Foreign relations -- 1984- -- Sources